Managing Academic Stress: Case Study of High School Students and Strategies in Biology Learning - Qisthi, Naufalia; Juniarti, Mia Angrianan; Hamdiyati, Yanti; Rahmat, Adi; Winarno, Nanang (Universitas Negeri Surabaya, 2024)
Abstract Background: Stress is a phenomenon that is often ignored in society because it is related to mental health. Academic stress is a subjective response to high academic demands and changes in the school environment. Objectve: These findings highlight the need for educational institutions to consider lesson timing to manage students' academic stress. Method: The research method used is quantitative descriptive. In data analysis, 40 students from one class were taken as samples using purposive sampling technique. The sample determined by the researcher was public and private high school students without gender restrictions. Result: The variable biology lesson hours has a significant correlation with students' academic stress levels, while gender does not have a significant correlation. The Kruskal Wallis test showed little difference in stress levels between biology lessons held in the morning or afternoon. Conclusion: Using the SEL approach can help educational institutions create learning environments that are more adaptive and responsive to students' needs in dealing with academic stress. Abstrak Latar Belakang: Stres merupakan fenomena yang sering diabaikan dalam masyarakat karena terkait dengan kesehatan mental. Stres akademik merupakan respons subjektif terhadap tuntutan akademik yang tinggi dan perubahan lingkungan sekolah. Tujuan: Temuan ini menyoroti perlunya institusi pendidikan mempertimbangkan pengaturan waktu pelajaran untuk mengelola stres akademik siswa. Method: Penelitian ini menggunakan metode deskriptif kuantitatif untuk mengeksplorasi tingkat stres akademik siswa Sekolah Menengah Atas pada pelajaran biologi. Metode penelitian yang digunakan yaitu deskriptif kuantitatif. Dalam analisis data, 40 siswa dari satu kelas diambil sebagai sampel menggunakan teknik purposive sampling. Sampel yang ditentukan oleh peneliti yaitu siswa SMA negeri dan swasta tanpa batasan jumlah gender. Hasil: Variabel jam pelajaran biologi memiliki korelasi signifikan dengan tingkat stres akademik siswa, sedangkan gender tidak memiliki korelasi signifikan. Uji Kruskal Wallis menunjukkan sedikit perbedaan dalam tingkat stres antara pelajaran biologi yang diadakan pada jam pagi atau siang. Simpulan: Penggunaan pendekatan SEL dapat membantu institusi pendidikan menciptakan lingkungan pembelajaran yang lebih adaptif dan responsif terhadap kebutuhan siswa dalam menghadapi stres akademik.